1986
DOI: 10.1111/j.1365-2265.1986.tb03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors in Graves' Ophthalmopathy

Abstract: We investigated the distribution of HLA and immunoglobulin G heavy chain markers (Gm) in 117 patients with Graves' disease, 62 with ophthalmopathy and 55 without. With Graves' disease per se, there is a closer association with HLA-DR3 than with B8. The opposite was true for Graves' patients with ophthalmopathy (odds ratio for ophthalmopathy associated with B8 was 12.4 and with DR3 was 7.7, both with P less than 0.0005). HLA-DR7 interacts with B8 in modifying the risk for eye disease; using the phenotype B8- DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 11 publications
1
33
0
2
Order By: Relevance
“…In addition, these heterozygotes were at an increased risk clinically for endocrine ophthalmopathy of grade II or higher. This may indicate that in a subgroup of GD patients there is a "heterozygosity effect" of distinct HLA markers that may contribute to the susceptibility of endocrine ophthalmopathy [11,12,14,21,27]. One might speculate that the presence or absence of critical amino acids of the HLA class II molecules may influence the repertoire of the organinfiltrating lymhocytes which then causes a distinct clinical picture [4,6,13,16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these heterozygotes were at an increased risk clinically for endocrine ophthalmopathy of grade II or higher. This may indicate that in a subgroup of GD patients there is a "heterozygosity effect" of distinct HLA markers that may contribute to the susceptibility of endocrine ophthalmopathy [11,12,14,21,27]. One might speculate that the presence or absence of critical amino acids of the HLA class II molecules may influence the repertoire of the organinfiltrating lymhocytes which then causes a distinct clinical picture [4,6,13,16].…”
Section: Discussionmentioning
confidence: 99%
“…15 Genes such as those for human leukocyte antigen and CTLA-4 genes may determine a patient's susceptibility to Graves' disease and ophthalmopathy and its severity. 16,17 …”
Section: Pathogenesismentioning
confidence: 98%
“…Taking advantage of the differences in tandem associations (linkage disequilibrium) between alíeles of loci of the MHC, we compared MHC-related predisposition to TAO in two white populations (28,29). In Hungarians, in whom B8 maintains a less close linkage disequilibrium with DR3 than it does with northern Europeans, we found that the former B locus alíele showed stronger association with B8 as compared with DR3.…”
Section: Introductionmentioning
confidence: 95%
“…In both calculations, double negatives for genetic markers were used as reference fb, homozygote for immunoglobulin heavy chain marker (Gm) haplotypes fb or fnb Modified from Frecker et al (28). The vast majority of the studies considered were retrospective and may have missed the natural historical curves that TAO pursues in individual patients.…”
Section: Introductionmentioning
confidence: 99%